Penanaman Nilai Spiritualitas Melalui Mujahadah Nihadlul Mustaghfirin Terhadap Pembentukan Karakter Santri Pondok Pesantren Tarbiyatul Islam Al-Falah Salatiga - Maghfiroh, Lailatul (Spiritualita, 2020)
Through this article the author provides an overview related to the cultivation of spiritual values through Mujahadah Nihadlul Mustaghfirin towards the character of santri in the PPTI Al-Falah Salatiga. In this study, it can be seen that the planting of spiritual values through mujahadah plans an important role in character building, especially among the santri of the Al-Falah Islamic boarding school. This research will focus on 1) the extent to which spiritual values are planted through mujahadah towards the formation of santri character, 2) inhibiting factors and supporting factors in the cultivation of spiritual values through Mujahadah Nihadlul Mustagfririn in the formation of santri characters. The research is using qualitative research by describing the implementation of Mujahadah in Al-Falah Islamic Boarding School. The results of the study show that the cultivation of spiritual values through Mujahadah really had a significant effect on the character of santri. Thus, the santri is able to have closeness with Allah so that he is able to rest in seeking knowledge and can have ahlakul karimah in dealing with humans (hablun min An-nas) and its relationship with the creator (hablun minallah). The supporting factors and obstacles are the enthusiasm of the students who want to add more value to their spirituality in order to be able to control themselves and be able to form better characters. The inhibiting factor is the lack of new santri about mujahadah and its purpose.